GONZÁLEZ-ESTEBAN, E. y SIURANA, J. C. (eds.) (2023). Inteligencia Artificial: concepto, alcance y retos. Valencia: Tirant lo Blanch - Saura García, Carlos (Daimon Revista Internacional de Filosofia, 2023)
Reseña de: GONZÁLEZ-ESTEBAN, E. y SIURANA, J. C. (eds.) (2023). Inteligencia Artificial: concepto, alcance y retos. Valencia: Tirant lo Blanch.